Women's Movements, Plural Legal Systems and the Botswana Constitution : How Reform Happens - Hasan, Tazeen; Tanzer, Ziona (World Bank, Washington, DC, 2014)
Collective action by women's networks has been a strong driver of legislative change in many countries across the world. Women's groups in Botswana have used advocacy tools such as testing the implementation of gender equality principles in the national court system. In 1992, women's legal networks in the Unity Dow case successfully challenged discriminatory statutory citizenship laws. This victory triggered far-reaching reforms of the citizenship law, family law, and even the Constitution itself. Two decades later, another successful "test" case, the Mmusi case, has challenged the customary law practice of favoring male heirs as contrary to constitutional principles of equality. The paper explores the role that judges and national courts play in implementing gender equality principles and upholding state commitments to the Convention on the Elimination of Discrimination against Women. The paper also highlights the role of governments in taking on the concerns of their citizens and cementing the principle of equality in national legal frameworks. The backdrop to this process is a plural legal system where both customary and statutory laws and courts exist side by side. How women negotiate their rights through these multiple systems by coalition building and using "good practice" examples from other countries is important to understand from a policy perspective and how this "bottom-up" approach can contribute to women's economic empowerment in other national contexts.